2009
DOI: 10.1002/path.2547
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic gene expression index in ovarian cancer—validation across different independent data sets

Abstract: Ovarian carcinoma has the highest mortality rate among gynaecological malignancies. In this project, we investigated the hypothesis that molecular markers are able to predict outcome of ovarian cancer independently of classical clinical predictors, and that these molecular markers can be validated using independent data sets. We applied a semi-supervised method for prediction of patient survival. Microarrays from a cohort of 80 ovarian carcinomas (TOC cohort) were used for the development of a predictive model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 20 publications
(26 reference statements)
1
88
0
Order By: Relevance
“…To test the benchmarking power of the TRRUST data, we used two inferred human TRNs: i) a published TRN inferred from a combined data set of ChIP-chip/seq from the hmChIP database33 and various related gene expression data using the ChIPXpress34 algorithm and; ii) an unpublished TRN inferred from a series of microarray samples from Gene Expression Omnibus (GEO)35 and GSE1476436 using the GENIE337 algorithm. The benchmarking power of a given set of TF-target interactions was assessed by their enrichment for each of successive bins of 1,000 inferred regulatory interactions, which were sorted by algorithm scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the benchmarking power of the TRRUST data, we used two inferred human TRNs: i) a published TRN inferred from a combined data set of ChIP-chip/seq from the hmChIP database33 and various related gene expression data using the ChIPXpress34 algorithm and; ii) an unpublished TRN inferred from a series of microarray samples from Gene Expression Omnibus (GEO)35 and GSE1476436 using the GENIE337 algorithm. The benchmarking power of a given set of TF-target interactions was assessed by their enrichment for each of successive bins of 1,000 inferred regulatory interactions, which were sorted by algorithm scores.…”
Section: Resultsmentioning
confidence: 99%
“…We combined those files to construct one example of a human TRN that comprises TF-target relationships ranked by score. We applied the GENIE3 algorithm37 to GSE1476436 microarray data to infer another example of a human TRN. More significant regulatory interactions have lower scores by the ChIPXpress algorithm and higher scores by the GENIE3 algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…To verify the prognostic power of the CLOVAR survival signature, we used ssGSEA to analyze 64 TCGA expression profiles not included in the training dataset and 815 expression profiles with matching survival annotation from 6 published studies (9,10,23,(29)(30)(31). CLOVAR survival signature ssGSEA scores were calculated for each of the 7 validation datasets.…”
Section: Gene Expression Profiles From Individual Hgs-ovca Tumor Sampmentioning
confidence: 99%
“…Many early generation ovarian cancer gene expression profiling studies focused primarily on the prognostic value of gene expression signatures. Results of these early prognostic gene expression studies [6][7][8][9][10][11][12][13][14] and those following [15][16][17][18][19][20][21][22][23][24][25] are summarized in Table 1 (Table 1). Most of these studies have identified a group of prognostically relevant genes in relatively small training sets but did, to their credit, validate the prognostic relevance of the respective gene signatures in independent cohorts.…”
Section: Gene Expression Signatures With Prognostic Relevancementioning
confidence: 99%